Evaluation of long-term carbon dynamics in a drained forested peatland using the ForSAFE-Peat model - D. Escobar; D. Escobar; S. Manzoni; J. Tapasco; P. Vestin; S. Belyazid (Biogeosciences)
Management of drained forested peatlands has important implications for carbon budgets, but contrasting views exist on its effects on climate. This study utilised the dynamic ecosystem model ForSAFE-Peat to simulate biogeochemical dynamics over two complete forest rotations (1951–2088) in a nutrient-rich drained peatland afforested with Norway spruce (Picea abies) in southwestern Sweden. Model simulations aligned well with observed groundwater levels (R2=0.78) and soil temperatures (R2≥0.76) and captured seasonal and annual net ecosystem production patterns, although daily variability was not always well represented. Simulated carbon exchanges (a positive sign indicates gains, and a negative sign indicates losses) were analysed considering different system boundaries (the soil; the ecosystem; and the ecosystem and the fate of harvested wood products, named ecosystem–HWP) using the net carbon balance (NCB) and the integrated carbon storage (ICS) metrics. Model results indicated negative NCB and ICS across all system boundaries, except for a positive NCB calculated by the end of the simulation at the ecosystem–HWP level. The soil exhibited persistent carbon losses primarily driven by peat decomposition. At the ecosystem level, net carbon losses were reduced as forest growth partially offset soil losses until harvesting. NCB was positive (2307 gC<mspace width="0.125em" linebreak="nobreak"/><msubsup>msoil-2</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="37pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="08c543144338314f4b10ced4437b56cb"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-2023-2025-ie00001.svg" width="37pt" height="17pt" src="bg-22-2023-2025-ie00001.png"/></svg:svg>) at the ecosystem–HWP level due to the slow decay of harvested wood products, but ICS was negative (-0.59×106<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="59pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="7373506b0fc74b809df7466427be02df"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-2023-2025-ie00002.svg" width="59pt" height="14pt" src="bg-22-2023-2025-ie00002.png"/></svg:svg> gC<mspace linebreak="nobreak" width="0.125em"/>yr<mspace linebreak="nobreak" width="0.125em"/><msubsup>msoil-2</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="47pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="51823c91fe35764f0b30cdb8d6a2dadf"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-2023-2025-ie00003.svg" width="47pt" height="17pt" src="bg-22-2023-2025-ie00003.png"/></svg:svg>) due to the large initial carbon losses. This study highlights the importance of system boundary selection and temporal dynamics in assessing the carbon balance of forested drained peatlands.